2020
DOI: 10.1002/jmv.26361
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal epidemiology of human coronavirus OC43 in Yamagata, Japan, 2010–2017: Two groups based on spike gene appear one after another

Abstract: Human coronavirus OC43 (HCoV-OC43) is divided into genotypes A to H based on genetic recombination including the spike (S) gene. To investigate the longitudinal transition of the phylogenetic feature of the HCoV-OC43 S gene in a community, phylogenetic analysis of the S1 region of the S gene was conducted using 208 strains detected in Yamagata during 2010 to 2017 with reference strains of the genotype. The S1 sequences were divisible into four groups: A to D. All Yamagata strains belonged to either group B or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…We constructed time-resolved phylogenies of the OC43 and 229E using publicly accessible sequenced isolates. A cursory look at these trees confirms previous reports that substantial diversity exists within each viral species ( Zhang et al, 2015 ; Komabayashi et al, 2020 ; Lau et al, 2011 ). Additionally, the trees form ladder-like topologies with isolate tips arranged into temporal clusters rather than geographic clusters, indicating a single global population rather than geographically isolated populations of virus.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…We constructed time-resolved phylogenies of the OC43 and 229E using publicly accessible sequenced isolates. A cursory look at these trees confirms previous reports that substantial diversity exists within each viral species ( Zhang et al, 2015 ; Komabayashi et al, 2020 ; Lau et al, 2011 ). Additionally, the trees form ladder-like topologies with isolate tips arranged into temporal clusters rather than geographic clusters, indicating a single global population rather than geographically isolated populations of virus.…”
Section: Resultssupporting
confidence: 86%
“…Additionally, two genetically distinct groupings (each of which include multiple of the aforementioned eight genotypes) of OC43 viruses have been shown to alternate in prevalence within a Japanese community, meaning that the majority of OC43 infections are caused by one group for about 2–4 years at which point the other group begins to account for the bulk of infections. It has been suggested that antigenic differences between these groups contribute to this epidemic switching ( Komabayashi et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…A cursory look at these trees confirms previous reports that substantial diversity exists within each viral species (Y. Zhang et al 2015; Komabayashi et al 2020; Lau et al 2011). Additionally, the trees form ladder-like topologies with isolate tips arranged into temporal clusters rather than geographic clusters, indicating a single global population rather than geographically-isolated populations of virus.…”
Section: Resultssupporting
confidence: 86%
“…We constructed time-resolved phylogenies of the OC43 and 229E using publicly accessible sequenced isolates. A cursory look at these trees confirms previous reports that substantial diversity exists within each viral species (Zhang et al 2015; Komabayashi et al 2020; Lau et al 2011). The phylogeny of OC43 bifurcates immediately from the root (Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation